(untitled) (Academicia Globe: Inderscience Research, 2024)
Artificial Intelligence (AI) has become an increasingly prevalent tool in education, offering numerous benefits to both teachers and students. By incorporating AI into school lessons, educators can enhance the learning experience and provide personalized instruction to meet the needs of individual students.